Plectranthus zeylanicus: A Rich Source of Secondary Metabolites with Antimicrobial, Disinfectant and Anti-Inflammatory Activities - Mayuri Napagoda; Jana Gerstmeier; Hannah Butschek; Sybille Lorenz; Sudhara De Soyza; Mallique Qader; Ajith Nagahawatte; Gaya Bandara Wijayaratne; Bernd Schneider; Aleš Svatoš; Lalith Jayasinghe; Andreas Koeberle; et al. (MDPI AG, 2022)
Plectranthus zeylanicus Benth is used in Sri Lankan folk medicine as a remedy for inflammatory conditions and microbial infections. Our previous investigations revealed potent 5-lipoxygenase (5-LO) inhibitory activity in lipophilic extracts of this plant, supporting its anti-inflammatory potential. In-depth studies on the antimicrobial activity have not been conducted and the bioactive ingredients remained elusive. As a continuation of our previous work, the present investigation was undertaken to evaluate the antimicrobial activity of different extracts of P. zeylanicus and to isolate and characterize bioactive secondary metabolites. Different organic extracts of this plant were analyzed for their antibacterial activity, and the most active extract, i.e., dichloromethane extract, was subjected to bioactivity-guided fractionation, which led to the isolation of 7α-acetoxy-6β-hydroxyroyleanone. This compound displayed strong antibacterial activity against methicillin-resistant Staphylococcus aureus with a minimum inhibitory concentration of 62.5 µg/mL, and its disinfectant capacity was comparable to the potency of a commercial disinfectant. Moreover, 7α-acetoxy-6β-hydroxyroyleanone inhibits 5-LO with IC50 values of 1.3 and 5.1 µg/mL in cell-free and cell-based assays, respectively. These findings rationalize the ethnopharmacological use of P. zeylanicus as antimicrobial and anti-inflammatory remedy.